(untitled) - Pence, Gregory E (Boston, 2007)
Includes bibliographical references (p. N1-N27) and index.; 1. Lying to patients and ethical relativism -- 2. Kant on whether alcoholism is a disease -- 3. Kant's critique of adult organ donation -- 4. Utilitarians vs. Kantians on stopping AIDS -- 5. Emotivism and banning some conceptions -- 6. Terri Schiavo : when does personhood end? -- 7. Are genetic abortions euugenic? -- 8. Can research be just on people with schizophrenia? -- 9. Is there a duty to die? -- 10. Treating Jehovah's Witnesses professionally.
Keywords: Bioethics; Ethics.; Medical ethics.; Đạo đức sinh học; Y đức; Đạo đức học